The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1183/09031936.03.00039102
|View full text |Cite
|
Sign up to set email alerts
|

Can early infection explain the sibling effect in adult atopy?

Abstract: Atopy is strongly and inversely related to family size, a pattern which is plausibly assumed to reflect a protective effect of early infection. The current study tested this hypothesis by case-referent analysis of an adult cohort in the UK.The study established that atopy, defined by prick tests to common aeroallergens, was less common among those from larger families after adjustment for potentially confounding factors. In particular, a higher number of brothers appeared to offer protection. The current autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 28 publications
4
45
1
Order By: Relevance
“…The "sibling effect", that children with more siblings have a lower risk of developing atopic disorders (Strachan, 1989), is the basic finding that the hygiene hypothesis comes from. The sibling effect on atopic disorders has been demonstrated in cohort studies (Benn et al, 2004;Matheson et al, 2009;Cullinan et al, 2003). A similar effect was reported in case of T1D (Cardwell et al, 2008a) and IBD (Koloski et al, 2008).…”
Section: Evidence Of the Hygiene Hypothesissupporting
confidence: 58%
See 2 more Smart Citations
“…The "sibling effect", that children with more siblings have a lower risk of developing atopic disorders (Strachan, 1989), is the basic finding that the hygiene hypothesis comes from. The sibling effect on atopic disorders has been demonstrated in cohort studies (Benn et al, 2004;Matheson et al, 2009;Cullinan et al, 2003). A similar effect was reported in case of T1D (Cardwell et al, 2008a) and IBD (Koloski et al, 2008).…”
Section: Evidence Of the Hygiene Hypothesissupporting
confidence: 58%
“…Therefore, the geographical distribution and/or chronological transition of some autoimmune diseases cannot be explained by the hygiene hypothesis. For atopic disorders, the sibling effect itself has been confirmed (Benn et al, 2004;Matheson et al, 2009;Cullinan et al, 2003). However, some authors suggest that infections in early life do not explain the observed sibling effect (Benn et al, 2004;Cullinan et al, 2003).…”
Section: Evidence That Does Not Match the Hygiene Hypothesismentioning
confidence: 95%
See 1 more Smart Citation
“…These studies have, however, brought up conflicting evidence. A number of surveys have shown protection of allergy whereas others could not confirm these results (Jarvis et al, 2004;Bodner et al, 2000;Cullinan et al, 2003). Hepatitis A might just be a marker of unhygienic environmental exposures rather than being a true culprit of the association.…”
Section: Other Viral Infections and Allergic Illnessesmentioning
confidence: 78%
“…Epidemiological evidence is strong, particularly with the dichotomous response seen by Fleming and Cook where a threshold infection prevalence of 10% of Trichuris trichiura appeared to suppress MS risk [15]. Strong associations are seen geographically, where the areas with the highest helminth burdens tend to be those with lowest autoimmune and allergic conditions, and in studies correlating allergic symptoms in childhood with exposure to factors such as farms, dogs, cats or overcrowding [16][17][18][19], any or all of which one could argue to be useful as surrogates for potential helminth infection. Similarly, a German study demonstrated a reduced risk of inflammatory bowel disease in subjects who spent greater amounts of time outside as part of their occupation [20].…”
mentioning
confidence: 99%